KRISTALINITAS DAN UKURAN NANOPARTIKEL ZnO YANG DIKALSINASI PADA TEMPERATUR 100oC dan 200oC - Hernowo, Alfian; Nurhasanah, Iis (BERKALA FISIKA, 2019)
The purpose of this researh is to analyze a crystalinity and size of zinc oxide (ZnO) nanoparticles. ZnO nanoparticles were synthesized using precipitation method followed by ultrasonic radiation. Precipitation products were calcined at temperature of 100oC and 200oC. ZnO nanoparticles were characterized using X-Ray Diffractometer (XRD) and Scanning Electron Microscope (SEM). The XRD pattern showed formation of ZnO nanoparticles with wurtzite hexagonal structure. ZnO nanoparticles with crystalinity higher than 50% was obtained at calcination temperature of 200oC. ZnO nanoparticles composed by a collection of crystallites that form spherical particle with size in the range 150–250 nm.Keywords: zinc oxide, nanoparticles, precipitation, crystal structure, crystallinity